Essential study skills - Wong, Linda (Houghton Mifflin, 1991)
Essential Study Skills, 5/e, provides in-depth coverage of study skills with ample room for practice and application. Appropriate for students at both 2-year and 4-year schools--including adult learners--this text can be adapted to any learning style and follows a step-by-step approach that guides students through the process of learning the skills necessary for college success.